Professional Competence as the Main Factor of Training Future Specialists in Graphic Design - Dongting, Ju (Professional Art Education, 2021)
The purpose of the article is to cover some aspects of professional training of future graphic designers. Methodology. The structure of the graphic designer’s readiness for professional activity is determined by: methodological (humanistic, cultural, creative) and pedagogical (cognitive, operational, personal) components, as well as creative and competence approach with its integral characteristics (visual, audio, kinesthetic). Highlighting the most important principles of teaching professional disciplines, namely: individual approach to students, clarity, system and consistency in solving educational tasks, it should be noted that they form a clear pedagogical system of training. A significant advantage of such a system is the formation of an individual who is aware of their creativity, creative potential, strong academic knowledge that was acquired during the study period. Scientific novelty. The organizational and methodological conditions of professional training of future designers are determined. The integration possibilities of general artistic and professionally oriented knowledge in the formation of a holistic system of skills of future graphic designers are pointed out. The role of the creative-competence approach in design education is substantiated along with its integral characteristic, which promotes the activation of creativity, the solution of creative tasks, helps in the professional training of future specialists in graphic design. Results. It is determined that professional competence forms an individual aspect of the future graphic designer’s readiness for professional development and is determined by the level of acquired professional knowledge, skills and abilities. Educational activities, which compose the process of acquiring this knowledge, the formation of skills (techniques) and abilities (methods of acquiring and using knowledge) affect the development and production of modern techniques used in the training of graphic designers. Understanding of artistic and pedagogical processes in design education and its bifurcation makes it possible to determine the relationship between fine arts and design and the opportunities that open up due to their development and their application in teaching. In modern conditions, teaching design at art and graphic faculties is experiencing a new stage of finding directions and universal interpretive paradigms. Artistic and technical design is developing especially fast, the main task of which is the creation of graphic objects, development of corporate style, logo, brand book, packaging design, etc. The creative aspect according to which the teaching of graphic design is aimed at the assimilation, preservation, dissemination of works of art, readiness to participate in their creation, dictates the need to highlight the specifics of training future professionals. An important role in the professional training of a graphic designer is played by the aspect of motivation, namely the creation of a new visual and communicative quality, which is achieved by forming a model of graphic design development. In the process of research the unity of theoretical and practical readiness for creative activity is singled out. Conclusions. The program competencies that students acquire in the process of professional training are defined. It was found that the multilevel application of visual communication refers to special training, and the general artistic aspect of training a graphic designer is a necessary component of a holistic system of their professional education and it forms the basis of fundamental knowledge of the specialist. The knowledge that the future graphic designer must acquire in the process of professional training includes the following components: general theoretical component (study of theoretical disciplines of humanities, historical and cultural, socio-psychological content); general art component (mastering the methods and techniques of image, knowledge of author’s graphic materials) professionally-oriented component (knowledge of the basics of project activities, special knowledge in the field of graphic design, 3D-modeling programs, implementation of projects using the material); organizational and technical component (systematization, use of information, research activities).